Menggagas Dakwah Penyelamatan Lingkungan - Fajar Hardoyono (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2009)
Environment has important role for supporting human activity. Basically, Environment gives resources which ishelpful for human activity to increase prosperity by exploring natural resources. As far as now, environmental qualitydegradation occurs in many countries in the world especially in Indonesia. Indonesia, one of the greatest forest areas andthe richest natural resources has been occurring environment degradation caused by irresponsible activity of many people.In several regions in Indonesia, people have to be ready for coming of natural disaster such as flood in rainy season anddrought in wet season, caused by degradation of environmental quality. Illegal logging, unsolvable rubbish management,and global warming are our problem today because we aren’t still fully aware about environment quality surrounding us.However, our religion has been teaching us about awareness in environment such us for keeping cleanness, not wasting ofrubbish arbitrarily, and conserve endangered animals and plants. How to improve our environment? Let’s go to campaignfor saving our environment